THE EFFECT OF DIFFERENT SOWING SCHEMES AND FEEDING NORMS ON SOIL WATER PERMEABILITY IN AMARANTH CROPS SOWN FOR GREEN MASS - Zikiryoeva Kamola Fayzullo kizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract. This article studies the effect of different sowing schemes and feeding rates on soil water permeability in amaranth (Amaranthus spp.) grown for green mass. The studies were conducted in 2023 at the end of the growing season in the 0–30 and 30–50 cm soil layers. Soil water permeability was determined for 6 hours, and the amount of water absorption was calculated for each hour. According to the results obtained, in all variants, the water absorption rate was high in the first hours and gradually decreased in the following hours. Planting schemes and feeding rates had a significant effect on soil water permeability. In particular, the water permeability in the 0–30 cm soil layer for a total of 6 hours was in the range of 797–879 units, and in the 30–50 cm layer it was 620–669 units. In the variants where relatively wider and optimal planting schemes are used, the soil permeability is high, which allows improving the water-air regime of the soil when growing amaranth for green mass. The results of the study are of scientific and practical importance in improving the agrotechnology of amaranth cultivation.